Synthesis and luminescent properties of bimetallic gold(I) and silver(I) pyrazolate complexes - Sabran, Nurul Husna (2015)
Luminescent d10 complexes of gold(I) and silver(I) have particularly received much attention due to their phosphorescent characteristics originating from metal– metal interactions and their applications in organic light–emitting diodes, sensors, catalysis, optics, and photonics. While bimetallic gold(I) and silver(I) complexes have been synthesized as clusters or mixed–compounds, luminescent studies of molecular self–assembly of bimetallic gold(I) and silver(I) complexes have not yet been reported. Therefore, this research aimed to study the phosphorescent properties of molecularly self–assembled trinuclear bimetallic gold(I) and silver(I) pyrazolate complexes (4[Au3Pz3]@[Ag3Pz3]R) using fluorescence spectroscopy. Both trinuclear gold(I) and silver(I) pyrazolate complexes, 2[Au3Pz3]R and 3[Ag3Pz3]R were successfully synthesized from pyrazole ligands having different alkyl chains (1(PzH)R; R = H, (OCH3)2Bn, (OC10TEG)3Bn) with chloro(dimethylsulfide) gold(I) ([Au(SMe2)]Cl) and silver(I) hexafluorophosphate (AgPF6). Bimetallic pyrazolate complexes 4[Au3Pz3]@[Ag3Pz3]R were synthesized by stirring a mixture of 2[Au3Pz3]R and 3[Ag3Pz3]R in dry dichloromethane for 1 hour with molar ratios of 2[Au3Pz3]R to 3[Ag3Pz3]R of 1:1, 1:2, 1:3, 1:5, 1:10, 2:1, 3:1, and 5:1, whereas molar ratios of 1:1, 1:2, and 2:1 were used for synthesis of (OC10TEG)3Bn. At molar ratio of 1:1, the fluorescence spectrum of the resulting complex exhibited only one emission peak centered at 633 nm compared to 691 nm for 2[Au3Pz3]H and 471 nm for 3[Ag3Pz3]H when excited at 280 nm. Based on the luminescent changes at molar ratio 1:1, it is proposed that the formed bimetallic complex might be the gold(I)– silver(I) cluster, 4[Au3Pz3]@[Ag3Pz3]H. On the other hand, the bimetallic pyrazolate complex obtained at molar ratio 1:1 was 4[Au3Pz3]@[Ag3Pz3](OCH3)2Bn when the alkyl chain was changed by (OCH3)2Bn. Two emission peaks at 463 and 606 nm were shown in fluorescence spectra where the intensity of the peak at 463 nm assigned to gold(I)–silver(I) interactions is relatively much lower in comparison to the peak at 606 nm of gold(I)–gold(I) interaction. The result obviously suggests molecular structural changes which may be associated to increase rigidity of side chain of the bimetallic complexes. When the alkyl chain was changed by (OC10TEG)3Bn, the resulting bimetallic amphiphilic complex, 4[Au3Pz3]@[Ag3Pz3](OC10TEG)3Bn with molar ratio 1:1 exhibited two emission peaks at 491 and 710 nm with almost the same intensity upon excitation at 276 nm, while 2[Au3Pz3](OC10TEG)3Bn and 3[Ag3Pz3](OC10TEG)3Bn showed emission peaks at 699 nm and 537 nm, corresponding to gold(I) and silver(I), respectively. These findings suggested the formation of bimetallic amphiphilic complex via self– assembly of alternating gold(I) and silver(I) complexes due to the more flexible amphiphilic alkyl chains. Of significance, the characteristic luminescent properties of 4[Au3Pz3]@[Ag3Pz3]R with different types of pyrazole ligands and molar ratios could be ascribed to changes of the gold(I)–silver(I) coordination in the self– assembled structures.